2021
DOI: 10.1212/nxi.0000000000001001
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 Among Patients With Multiple Sclerosis

Abstract: ObjectiveWe systematically reviewed the literature on COVID-19 in patients with multiple sclerosis (MS).MethodsWe searched PubMed, Scopus, EMBASE, CINAHL, Web of Science, Google Scholar, and World Health Organization database from December 1, 2019, to December 18, 2020. Three conference abstract databases were also searched. We included any types of studies that reported characteristics of patients with MS with COVID-19.ResultsFrom an initial 2,679 publications and 3,138 conference abstracts, 87 studies (67 pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 43 publications
(76 reference statements)
5
69
6
1
Order By: Relevance
“…In late 2019, an outbreak due to a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) led to the coronavirus disease 2019 (COVID-19) global pandemic and claimed many lives, especially in patients with comorbidities [ 1 ]. Early reports suggested that individuals with multiple sclerosis (MS) had an increased risk for a worse outcome after contracting COVID-19, based on certain disease characteristics and treatments [ 2 4 ] while other studies disputed these claims [ 5 7 ]. A recent study suggested no significant effects on MS relapse rates after COVID-19 infection [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In late 2019, an outbreak due to a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) led to the coronavirus disease 2019 (COVID-19) global pandemic and claimed many lives, especially in patients with comorbidities [ 1 ]. Early reports suggested that individuals with multiple sclerosis (MS) had an increased risk for a worse outcome after contracting COVID-19, based on certain disease characteristics and treatments [ 2 4 ] while other studies disputed these claims [ 5 7 ]. A recent study suggested no significant effects on MS relapse rates after COVID-19 infection [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review, the most common symptoms of COVID-19 in patients with MS were as follows: fever (68.8%), cough (63.9%), fatigue/asthenia (51.2%), and dyspnea (39.5%) [ 65 ]. In total, only 5.3% of patients were asymptomatic.…”
Section: Ms and Covid-19mentioning
confidence: 99%
“…Again, it should be noted that diseased patients receiving B-cell-depleting therapies were also at higher ages and presented a severe degree of disability. Notwithstanding, more established investigations are required [ 65 , 67 ].…”
Section: Ms and Covid-19mentioning
confidence: 99%
See 2 more Smart Citations